Neutrophil extracellular traps (NETs) reduce the diffusion of doxorubicin which may attenuate its ability to induce apoptosis of ovarian cancer cells. Issue 6 (June 2022) - Tamura, Kohei; Miyato, Hideyo; Kanamaru, Rihito; Sadatomo, Ai; Takahashi, Kazuya; Ohzawa, Hideyuki; Koyanagi, Takahiro; Saga, Yasushi; Takei, Yuji; Fujiwara, Hiroyuki; Lefor, Alan Kawarai; Sata, Naohiro; et al.
Abstract: Purpose: Although neutrophil extracellular traps (NETs) are present in various tumors, their roles in tumor biology have not been clarified yet. In this study, we examined how NETs affect the pharmacokinetics and effects of doxorubicin (DOX). Methods: NETs were generated by neutrophils stimulated with phorbol 12-myristate 13-acetate (PMA) or lipopolysaccharide (LPS). DOX was added to NETs and their distribution was observed under fluorescein microscopy, and the diffusion of DOX through 3 μM pores from lower to upper chambers was evaluated with a fluorescence-based assay. Ovarian cancer cells, KOC-2S and SKOV3, were embedded in collagen gel droplets and cultured in 3D way and their apoptosis was examined with flow cytometry. Results: DOX was mostly co-localized with NETs. The transfer of DOX to upper chambers increased over time, which was significantly decreased by the presence of neutrophils stimulated with PMA or LPS in the lower chamber. DOX outside of the gel increased the rates of annexin V (+) apoptotic cells, which were significantly reduced by the addition of LPS-stimulated neutrophils in media both in KOC-2S and SKOV3. The reduced diffusion and apoptosis were mostly restored by the destruction of the NETs structure with 1000 u/ml DNAse I. Conclusion: NETs efficiently trap and inhibit the diffusion of DOX which may attenuate its ability to induce apoptosis of ovarian cancer cells. Degradation of NETs with DNAse I may augment the response of ovarian cancer to DOX. Highlights: Doxorubicin is efficiently trapped by neutrophil extracellular traps (NETs). NETs suppress diffusion of doxorubicin through micro-pores and infiltration into resected tumor. NETs suppress doxorubicin-induced apoptosis of tumor cells in 3-D culture. DNAse may augment the effect of anti-cancer drugs by modulating pharmacokinetics. Abstract : Neutrophil extracellular traps; doxorubicin; chemosensitivity; pharmacokinetics.